Delayed splenic rupture 4 months following minor blunt abdominal traumaChatzipetrou Maria, Tzanakis Nickolaos, Giannopoulos George and Kornaropoulos Michail* - Chatzipetrou Maria; Tzanakis Nickolaos; Giannopoulos George; Kornaropoulos Michail (Global Journal of Rare Diseases - Peertechz Publications, 2021)
Splenic rupture, no matter what the cause is, is associated with significant mortality. It can present either acutely after trauma, or days to weeks later, a situation known as ''delayed splenic rupture (DSR)''. On the other hand, splenic rupture without trauma history occurs mainly in a pathologically altered spleen, a rare situation called atraumatic splenic rupture (ASR). Cases of ASR of normal spleen have been reported in literature with various cause as far as trauma is concerned.